Dialogue and rhetoric - Weigand, Edda (Dialogue studies, 2008)
The volume deals with the relationship between dialogue and rhetoric. The actual state of the art in dialogue analysis is characterized by a tendency to overcome the distinction between competence and performance and to combine components from both sides of the dichotomy, in a way which includes rules as well as inferences. The same is true of rhetoric: the guidelines proposed here no longer state that rationality and persuasion are mutually exclusive but suggest that they interact in what might be called the 'mixed game'. The concept of a dialogic rhetoric thus poses the question of how to in.